The dialogism of ritual poetry and its expression and function in the Tuvan yoreels and algyshes - Prosyannikova, Olga I.; Skorik, Kseniya V.; Kuzhuget, Shenne Yu. (The New Research of Tuva, 2022)
The article examines the linguistic means of actuializing dialogism in the texts of Tuvan ritual poetry, with a special focus on good wishes (yoreel) and Shamanic cult incantations (algysh). Both genres come as a verbal component of a cultural or healing ritual and are performed monologically. However, they also preserve dialogical features, with dialogism appearing as interaction between their speaker and addressee. Subjects of these dialogical relationship have been described in the article, as well as the ways they can be made explicit in the text. It was discovered that dialogism is activated by different means, such as direct appeals, different forms of the imperative mood with the semantics of inducement to perform an action, the question-answer combination, question sentences of different functional and stylistic types, the "we"-forms, bringing together both subjects of the dialogue and calling on them for a joint action. The details of using the imperative, depending on the speaker and the verb semantics, have also been studied. The article also examines a variety of functions the dialogism performs, such as the pragmatic, appellative, and phatic, as well as the function to describe the relations between the subjects in a dialogue. All in all, the linguistic means of implementing these functions are also identified, and the performative verbs which act as a specific means of explication.